Effect of Preoperative N-Acetylcysteine on Postoperative Blood Loss Parameters in Cardiac Surgery Patients - Amber R. Wesner; Marcia L. Brackbill; Christine S. Sytsma (International Journal of Vascular Medicine)
Purpose. To determine if recent preoperative exposure to n-acetylcysteine (NAC), Mucomyst, increases postoperative blood loss in cardiac surgery patients. Methods. Retrospective review of cardiac surgery patients who underwent a cardiac catheterization within four days of surgery and whose serum creatinine was ≥1.0 mg/dL. The study groups were those who received NAC in the pericatheterization period versus those who did not. The primary endpoint was postoperative chest tube output at 24, 48, and 72 hours. Secondary endpoints included number of transfusions and other bleeding parameters. Results. Mean blood loss in the first 24 hours was 962 ± 595 mL in the treatment group (n=79) and 1,178 ± 788 mL in the control group (n=106), P=.040. Blood loss between groups at 48 (366 ± 318 mL versus 412 ± 363 mL, P=.382) and 72 (194 ± 300 mL versus 176 ± 224 mL, P=.643) hours was not significantly different. There were no significant differences in postoperative transfusions or other bleeding parameters. Conclusions. Preoperative exposure to NAC did not increase postoperative blood loss or negatively affect other bleeding parameters.